CURRENT TEACHING SITUATION AND POSSIBILITIES OF OMBROTHERMIC DIAGRAM AS DIGITAL SOURCE - Daniel David Martínez Romera (Didáctica Geográfica)
INTRODUCCIÓN: The main purpose of the present paper is to check how fits Geography technical basis with technological offer available on the Net, having in mind freeware or open source apps only; And, if needed, to design and to build a free digital resource in order to bridge that gap. For us, the starting point is the tradeoff between time spent and scientific accuracy in the classroom. Regardless of the academic level deemed, every teacher is facing this sensitive issue: the longer technical or epistemological questions requires the less contents can be taught. So, in fact, curricular thoroughness tips the balance towards itself, weakening the technical and epistemological aspects. In such context, the specific didactics, such as in the case of Geography, seek new forms of teaching and learning in the ICT world that allows to achive at least: an active role of the students, according to Ausubel, an analytic defiance, in the terms of Vygotsky, and a efficient man-machine interaction, retaking Licklider’s ideas.